Discrete hotelling pure location games: potentials and equilibria - Iimura, Takuya; von Mouche, Pierre (ESAIM. Proceedings and surveys, 2021)
We study two-player one-dimensional discrete Hotelling pure location games assuming that demand f ( d ) as a function of distance d is constant or strictly decreasing. We show that this game admits a best-response potential. This result holds in particular for f ( d ) = w d with 0 < w ≤ 1. For this case special attention will be given to the structure of the equilibrium set and a conjecture about the increasingness of best-response correspondences will be made. Nous étudions les jeux de localisation pure Hotelling discrets unidimensionnels à deux joueurs en supposant que la demande f ( d ) en fonction de la distance d est constante ou strictement décroissante. Nous montrons que ce jeu admet un potentiel de meilleure réponse. Ce ŕesultat vaut notamment pour f ( d ) = w d avec 0 < w ≤ 1. Dans ce cas, une attention particulière sera accordée à la structure de l’ensemble d’équilibre et une conjecture sur la croissance de la correspondance de meilleure réponse sera faite.